Composite current collector, preparation method thereof and secondary battery
By coating a nickel-chromium alloy barrier layer onto a carbon fiber substrate and depositing a metal layer, the stability and bonding issues of the composite current collector were solved, achieving uniform coating of the active material and improved electrode performance.
Patent Information
- Application Number
- CN202511397088.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2026-01-09
AI Technical Summary
Existing composite current collectors suffer from problems such as poor stability of polymer films, weak bonding with metal layers, easy peeling of carbon fiber fabrics, increased resistance of metal layers, and uneven coating of active materials.
A nickel-chromium alloy barrier layer is coated on a carbon fiber substrate, and a metal layer is deposited on it. A continuous and flat metal layer is formed by magnetron sputtering and pulse electroplating processes to fill the pores of the substrate.
This improves the chemical stability and mechanical strength of the composite current collector, enhances the adhesion between the metal layer and the substrate, and ensures the uniformity of the active material coating and the conductivity of the electrode.
Smart Images

Figure CN121307044A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of composite current collector technology, and in particular to composite current collectors and their preparation methods, and secondary batteries. Background Technology
[0002] Composite current collectors have advantages such as high safety, light weight, high energy density and low cost.
[0003] Reports have indicated the use of polymer films as the substrate for composite current collectors. These films are typically made of materials such as polyethylene terephthalate (PET) or polypropylene (PP), with metal layers deposited on both sides. However, polymer films suffer from poor stability or weak adhesion to the metal layers. For example, PET substrates are not resistant to electrolyte corrosion and exhibit poor chemical stability; PP substrates have poor adhesion to the metal layers, resulting in insufficient mechanical strength of the current collector.
[0004] Unlike the aforementioned polymer films, there are also reports of using carbon fiber fabrics with excellent conductivity and mechanical properties as the substrate for composite current collectors.
[0005] However, the following problems still exist when using carbon fiber fabric as a substrate: (1) the bonding force between metal and carbon fiber is poor, and peeling is easy to occur during battery cycling; (2) metal atoms and carbon atoms will diffuse into each other, affecting the strength of carbon fiber and causing the resistance of the metal layer to increase; (3) carbon fiber fabric has a three-dimensional porous structure, making it difficult to prepare a smooth metal layer on it, which affects the uniformity of subsequent active material coating; (4) carbon fiber is still not resistant to electrolyte corrosion. Summary of the Invention
[0006] Based on this, this application provides a composite current collector and its preparation method, as well as a secondary battery, to solve the above-mentioned technical problems.
[0007] A first aspect of this application provides a composite current collector comprising: a substrate having a three-dimensional porous structure formed by interwoven carbon fibers; a barrier layer covering the surface of the carbon fibers, the barrier layer comprising a nickel-chromium alloy; and a metal layer disposed on the side of the barrier layer away from the carbon fibers, at least a portion of the metal layer filling the pores of the substrate.
[0008] In some embodiments, the nickel-chromium alloy satisfies at least one of the following conditions: (1) the average grain size of the nickel-chromium alloy is 10 nm to 20 nm; (2) the mass ratio of nickel to chromium in the nickel-chromium alloy is (70 to 80): (20 to 30).
[0009] In some embodiments, the metal layer includes: a seed layer disposed on the surface of the barrier layer; and a conductive host layer disposed on the surface of the seed layer.
[0010] In some implementations, the thickness of the seed layer is 20 nm to 50 nm.
[0011] In some embodiments, the composite current collector satisfies at least one of the following conditions: (1) the thickness of the barrier layer is 5 nm to 20 nm; (2) the surface roughness Ra of the metal layer is less than 1 μm; (3) the thickness of the substrate is 4 μm to 10 μm; (4) the thickness of the metal layer is 0.5 μm to 2 μm; (5) the diameter of the carbon fiber is 3 μm to 7 μm; (6) the density of the substrate is 1 g / cm³. 3 ~2 g / cm 3 (7) The porosity of the substrate is 20%~70%.
[0012] A second aspect of this application provides a method for preparing a composite current collector, the method comprising the following steps: providing a substrate having a three-dimensional porous structure formed by interwoven carbon fibers; using a first magnetron sputtering process to deposit on both sides of the substrate to form a barrier layer on the surface of the carbon fibers, the barrier layer comprising a nickel-chromium alloy; and depositing a metal layer on the surface of the barrier layer such that the metal layer at least partially fills the pores of the three-dimensional porous structure.
[0013] In some embodiments, the first magnetron sputtering process satisfies at least one of the following conditions: (1) the number of targets in the first magnetron sputtering process is 1 to 3; (2) the sputtering power of the first magnetron sputtering process is 15 kW to 20 kW.
[0014] In some embodiments, depositing a metal layer on the barrier layer specifically includes the following steps: depositing a seed layer on the barrier layer using a second magnetron sputtering process; and depositing a conductive host layer on the seed layer using a pulse electroplating process.
[0015] In some embodiments, the preparation method satisfies at least one of the following conditions: (1) the number of targets in the second magnetron sputtering process is 4 to 10; (2) the sputtering power of the second magnetron sputtering process is 5 kW to 10 kW; (3) the peak current density of the pulse electroplating process is 1 ASD to 3 ASD; (4) the average current density of the pulse electroplating process is 0.2 ASD to 0.8 ASD; (5) the on-time of the pulse electroplating process is 1 ms to 10 ms; (6) the off-time of the pulse electroplating process is 5 ms to 50 ms; (7) the duty cycle of the pulse electroplating process is 10% to 20%.
[0016] A third aspect of this application provides a secondary battery comprising the composite current collector provided in the first aspect above, or the composite current collector prepared by the method for preparing the composite current collector provided in the second aspect above.
[0017] Compared with traditional technologies, the composite current collectors provided in some embodiments of this application have at least the following beneficial effects:
[0018] First, the nickel-chromium alloy used as the barrier layer exhibits excellent oxidation and corrosion resistance. Chromium atoms in the barrier layer can form covalent bonds with carbon atoms on the carbon fiber surface, generating stable chromium carbides at battery operating temperatures, thus improving the chemical stability of the interface. Simultaneously, nickel atoms in the barrier layer can form solid solutions with some metal atoms in the metal layer (such as copper and nickel atoms), enhancing interfacial compatibility and adhesion, and effectively reducing the risk of delamination between the substrate and the metal layer during cycling.
[0019] Secondly, the barrier layer can prevent the interdiffusion between metal atoms and carbon atoms, and with its resistance to electrolyte corrosion, it can prevent carbon fibers from being eroded by the electrolyte, thereby significantly improving the long-term stability of the composite current collector.
[0020] Furthermore, the barrier layer covering the carbon fiber can serve as a growth site for metal deposition, promoting the deep filling and continuous growth of the metal layer in the pores, thereby forming a continuous and smooth surface. This is beneficial for the uniform coating of the subsequent active material layer, improving the overall conductivity and fabrication consistency of the electrode.
[0021] In summary, this invention improves the long-term stability of the composite current collector and the uniformity of the active material coating by introducing a nickel-chromium alloy barrier layer between the carbon fiber substrate and the metal layer. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments or related technologies of this application, the accompanying drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a schematic diagram of the composite current collector in one embodiment of this application.
[0024] Figure 2 This is a schematic diagram of a method for preparing a composite current collector according to an embodiment of this application.
[0025] Explanation of reference numerals in the attached figures
[0026] 1. Composite current collector; 10. Substrate; 11. Carbon fiber; 20. Barrier layer; 30. Metal layer. Detailed Implementation
[0027] A detailed reference is now provided to embodiments of this application, one or more of which are described below. Each embodiment is provided for explanation and not for limitation. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.
[0028] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.
[0029] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0030] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0031] In this article, when referring to units of data ranges, if a unit is only followed by the right endpoint, it means that the units of the left and right endpoints are the same.
[0032] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0033] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0034] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0035] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0036] Combination Figure 1 As shown, in a first aspect, this application provides a composite current collector 1, which includes a substrate 10, a barrier layer 20, and a metal layer 30. The substrate 10 has a three-dimensional porous structure formed by interwoven carbon fibers 11. The barrier layer 20 covers the surface of the carbon fibers 11 and comprises a nickel-chromium alloy. The metal layer 30 is disposed on the side of the barrier layer 20 away from the carbon fibers 11, and at least a portion of the metal layer 30 fills the pores of the substrate 10.
[0037] The composite current collector 1 provided in some embodiments of this application has at least the following beneficial effects:
[0038] First, the nickel-chromium alloy used as the barrier layer 20 exhibits excellent oxidation and corrosion resistance. Chromium atoms in the barrier layer 20 can form covalent bonds with carbon atoms on the surface of the carbon fiber 11, generating chromium carbides that are stable at the battery operating temperature, thereby improving the chemical stability of the interface. Simultaneously, nickel atoms in the barrier layer 20 can form solid solutions with some metal atoms (such as copper and nickel atoms) in the metal layer 30, enhancing the compatibility and bonding strength of the interface and effectively reducing the risk of delamination between the substrate 10 and the metal layer 30 during cycling.
[0039] Secondly, the barrier layer 20 can prevent the interdiffusion between metal atoms and carbon atoms, and with its resistance to electrolyte corrosion, it can prevent the carbon fiber 11 from being eroded by the electrolyte, thereby significantly improving the long-term stability of the composite current collector 1.
[0040] Furthermore, the coating of carbon fiber 11 by barrier layer 20 can serve as a growth site for metal deposition, promoting the deep filling and continuous growth of metal layer 30 in the pores, thereby forming a continuous and flat surface, which is beneficial for the uniform coating of subsequent active material layers and improves the overall conductivity and fabrication consistency of the electrode.
[0041] In summary, the present invention improves the long-term stability of the composite current collector 1 and the uniformity of the active material coating by introducing a nickel-chromium alloy barrier layer 20 between the carbon fiber substrate 10 and the metal layer 30.
[0042] In some embodiments, the average grain size of the nickel-chromium alloy is 10 nm to 20 nm. Exemplarily, the average grain size of the nickel-chromium alloy can be, but is not limited to, 10 nm, 12 nm, 15 nm, 18 nm, or 20 nm. Within the above grain size range, the nickel-chromium alloy provides sufficient specific surface area to provide adsorption and nucleation sites for metal filling, while avoiding complete filling of the pores of the substrate 10, leaving space for the filling of the metal layer 30.
[0043] In some embodiments, the mass ratio of nickel to chromium in the nickel-chromium alloy is (70-80):(20-30). Exemplarily, the mass ratio of nickel to chromium in the nickel-chromium alloy can be, but is not limited to, 70:20, 70:25, 70:30, 75:20, 75:25, 75:30, 80:20, 80:25, and 80:30. A higher nickel content facilitates the formation of a solid solution between nickel atoms and metal atoms in the metal layer 30, thereby improving interfacial compatibility. Simultaneously, an appropriate amount of chromium allows chromium atoms to react with carbon atoms on the surface of the carbon fiber 11 to form stable carbides, enhancing the interfacial bonding and chemical stability between the carbon fiber 11 and the barrier layer 20.
[0044] In some embodiments, the metal layer 30 is made of a single metal or alloy of copper, aluminum, nickel, chromium, or titanium.
[0045] Furthermore, the metal layer 30 is made of a single metal or alloy of copper and nickel. This allows it to form a solid solution with the nickel atoms of the nickel-chromium alloy in the barrier layer 20, improving compatibility.
[0046] In some embodiments, the metal layer 30 includes a seed layer and a conductive host layer. The seed layer is disposed on the surface of the barrier layer 20. The conductive host layer is disposed on the surface of the seed layer. Specifically, the seed layer is made of a single metal or alloy of copper, aluminum, nickel, chromium, and titanium, and the conductive host layer can also be made of a single metal or alloy of copper, aluminum, nickel, chromium, and titanium.
[0047] In some embodiments, the thickness of the seed layer is 20 nm to 50 nm. Exemplarily, the thickness of the seed layer can be, but is not limited to, 20 nm, 30 nm, 40 nm, or 50 nm. Within the above thickness range, the seed layer can block the center of the pores in the substrate 10, so that the depth of the pores is fully filled and a continuous conductive channel is formed, thereby ensuring the flatness and continuity of the conductive body layer.
[0048] In some embodiments, the thickness of the barrier layer 20 is 5 nm to 20 nm. Exemplarily, the thickness of the barrier layer 20 can be, but is not limited to, 5 nm, 10 nm, 15 nm, or 20 nm. Within the above thickness range, the barrier layer 20 can effectively cover the surface of the carbon fiber 11, enhance the interfacial bonding force, and at the same time prevent the metal atoms and carbon atoms from diffusing into each other, maintaining a continuous and uniform conductive interface.
[0049] In some embodiments, the surface roughness Ra of the metal layer 30 is less than 1 μm. This lower surface roughness allows for the formation of a smooth and uniform metal surface, maintaining a continuous conductive interface, which is beneficial for the uniform coating of the active material layer and improves the electrode's conductivity and fabrication consistency.
[0050] In some embodiments, the thickness of the substrate 10 is 4 μm to 10 μm. Exemplarily, the thickness of the substrate 10 can be, but is not limited to, 4 μm, 6 μm, 8 μm, or 10 μm. Within the above thickness range, the substrate 10 can provide sufficient mechanical support and porosity stability while maintaining a continuous and uniform interface between the barrier layer 20 and the metal layer 30.
[0051] In some embodiments, the thickness of the metal layer 30 is 0.5 μm to 2 μm. For example, the thickness of the metal layer 30 can be, but is not limited to, 0.5 μm, 1 μm, 1.5 μm, or 2 μm. Within the above thickness range, both the continuity and conductivity of the metal layer 30 can be ensured, while simultaneously improving the mechanical strength of the composite current collector 1.
[0052] In some embodiments, the diameter of the carbon fiber 11 is 3 μm to 7 μm. Exemplarily, the diameter of the carbon fiber 11 can be, but is not limited to, 3 μm, 4 μm, 5 μm, 6 μm, and 7 μm. Within the above diameter range, the carbon fiber 11 can form a stable three-dimensional porous structure, balancing the porosity and mechanical strength of the substrate 10, providing favorable conditions for the filling of the metal layer 30 and the formation of the conductive network.
[0053] In some embodiments, the density of substrate 10 is 1 g / cm³. 3 ~2 g / cm 3 For example, the density of substrate 10 may be, but is not limited to, 1 g / cm³. 3 1.1 g / cm 3 1.2 g / cm 3 1.3 g / cm 3 1.4 g / cm 3 1.5 g / cm 3 1.6 g / cm 3 1.7 g / cm 3 1.8 g / cm3 1.9 g / cm 3 2 g / cm 3 The density of substrate 10 is controlled within this range, lower than that of copper foil and aluminum foil (the density of copper foil is 8.96 g / cm³). 3 The density of the aluminum foil is 2.7 g / cm³. 3 This can reduce the mass of the composite current collector 1 and increase its energy density, while also taking into account the porosity and mechanical strength of the substrate 10, thus providing favorable conditions for the filling of the metal layer 30 and the formation of the conductive network.
[0054] In some embodiments, the porosity of the substrate 10 is 20% to 70%. Exemplarily, the porosity of the substrate 10 can be, but is not limited to, 20%, 30%, 40%, 50%, 60%, 70%, and 80%. Within the above porosity range, the three-dimensional porous structure of the substrate 10 can improve the bonding force between the substrate 10 and the metal layer 30, and also increase the specific surface area of the composite current collector 1, thereby increasing the number of active sites.
[0055] Furthermore, the porosity of the substrate 10 is 50%~70%. The high porosity allows the metal layers 30 at both ends of the substrate 10 to conduct during the processing of the composite current collector 1, which can further reduce the resistance of the composite current collector 1.
[0056] Specifically, the weaving method of the substrate 10 includes plain weave (porosity 30%~50%), twill weave (porosity 40%~60%), satin weave (porosity 50%~70%), unidirectional weave (porosity 20%~60%), etc.
[0057] Combination Figure 2 As shown, a second aspect of this application provides a method for preparing a composite current collector, the method comprising the following steps:
[0058] S1. Provide a substrate with a three-dimensional porous structure formed by interwoven carbon fibers.
[0059] S2. Using a first magnetron sputtering process, deposits are made on both sides of the substrate to form a barrier layer on the surface of the carbon fiber, the barrier layer comprising a nickel-chromium alloy.
[0060] S3. Deposit a metal layer on the surface of the barrier layer away from the carbon fiber, such that the metal layer at least partially fills the pores of the three-dimensional porous structure.
[0061] In some embodiments, the number of targets in the first magnetron sputtering process is 1 to 3. For example, the number of targets in the first magnetron sputtering process can be 1, 2, or 3.
[0062] In some embodiments, the sputtering power of the first magnetron sputtering process is 15 kW to 20 kW. Exemplarily, the sputtering power of the first magnetron sputtering process can be, but is not limited to, 15 kW, 16 kW, 17 kW, 18 kW, 19 kW, or 20 kW.
[0063] The first magnetron sputtering process used for the barrier layer employs a short-time (fewer target materials) and high-power sputtering technique. This allows high-energy particles to generate an injection effect and strong bonding force when they collide with the three-dimensional surface formed by the interwoven carbon fibers, preferentially depositing on the windward and outer surfaces of the substrate. Magnetron sputtering is performed on both sides of the substrate separately, ultimately resulting in a barrier layer covering the carbon fibers, forming a continuous barrier layer structure that provides a stable interface foundation for the subsequent filling of the metal layer.
[0064] In some implementations, depositing a metal layer on the barrier layer specifically includes the following steps:
[0065] S31. A seed layer is deposited on the barrier layer using a second magnetron sputtering process.
[0066] S32. A conductive host layer is deposited on the seed layer using a pulse electroplating process.
[0067] The seed layer deposited using the second magnetron sputtering process can cover the surface of the barrier layer and deposit into the pore center of the substrate (since the carbon fiber of the substrate is cylindrical, the pore size of the substrate gradually decreases from the outside to the inside in the thickness direction, allowing the pore center to be filled), forming a continuous conductive channel, which provides a basis for the uniform growth of the subsequent conductive host layer; the conductive host layer deposited using the pulse electroplating process, through the periodic current action, makes the metal atoms more inclined to deposit at the lowest energy position rather than randomly nucleating, thus fully filling the pore depth of the three-dimensional porous structure of the substrate, forming a flat and continuous surface, which is conducive to the uniform coating of the subsequent active material layer, improving the overall conductivity and fabrication consistency of the electrode.
[0068] In some embodiments, the number of targets in the second magnetron sputtering process is 4 to 10. For example, the number of targets in the second magnetron sputtering process can be, but is not limited to, 4, 5, 6, 7, 8, 9, or 10.
[0069] In some implementations, the sputtering power of the second magnetron sputtering process is 5 kW to 10 kW. For example, the sputtering power of the second magnetron sputtering process can be, but is not limited to, 5 kW, 6 kW, 7 kW, 8 kW, 9 kW, and 10 kW.
[0070] The second magnetron sputtering process used for the seed layer employs a long-duration (large number of target materials) and high-power sputtering process, enabling the seed layer to cover the surface of the barrier layer and deposit into the pore center of the substrate, forming a continuous conductive channel, which provides a basis for the uniform growth of the subsequent conductive body layer.
[0071] In some implementations, the peak current density of the pulse electroplating process is 1 ASD to 3 ASD. For example, the peak current density of the pulse electroplating process can be, but is not limited to, 1 ASD, 2 ASD, or 3 ASD.
[0072] In some embodiments, the average current density of the pulse electroplating process is 0.2 ASD to 0.8 ASD. Exemplarily, the average current density of the pulse electroplating process can be, but is not limited to, 0.2 ASD, 0.3 ASD, 0.4 ASD, 0.5 ASD, 0.6 ASD, 0.7 ASD, or 0.8 ASD.
[0073] Within the aforementioned current density range, the deposition process is primarily controlled by electrochemical reactions rather than diffusion processes, which is beneficial for achieving dense and uniform metal deposition and avoiding insufficient deposition within pores, thereby ensuring the continuity and smoothness of the metal layer.
[0074] In some implementations, the conduction time of the pulse electroplating process is 1 ms to 10 ms. For example, the conduction time of the pulse electroplating process can be, but is not limited to, 1 ms, 2 ms, 3 ms, 4 ms, 5 ms, 6 ms, 7 ms, 8 ms, 9 ms, and 10 ms.
[0075] In some implementations, the turn-off time of the pulse electroplating process is 5 ms to 50 ms. Exemplarily, the turn-off time of the pulse electroplating process can be, but is not limited to, 5 ms, 10 ms, 15 ms, 20 ms, 25 ms, 30 ms, 35 ms, 40 ms, 45 ms, and 50 ms. Within the above-mentioned turn-off time range, metal atoms are allowed sufficient time to migrate on the surface and find lattice positions, thereby promoting two-dimensional layered growth (i.e., epitaxial growth) rather than three-dimensional island growth, forming a continuous, dense, and flat conductive host layer.
[0076] In some embodiments, the duty cycle of the pulse electroplating process is 10% to 20%. Exemplarily, the duty cycle of the pulse electroplating process can be, but is not limited to, 10%, 12%, 14%, 16%, 18%, and 20%.
[0077] A third aspect of this application provides a secondary battery comprising the composite current collector provided in the first aspect above, or the composite current collector prepared by the method for preparing the composite current collector provided in the second aspect above.
[0078] It is understandable that composite current collectors can be used as positive or negative current collectors in secondary batteries.
[0079] A fourth aspect of this application provides an electrical device comprising the secondary battery provided in the third aspect above.
[0080] The present application will now be described in detail with reference to specific embodiments and comparative examples.
[0081] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0082] Example 1
[0083] This embodiment provides a method for preparing a composite current collector.
[0084] (1) A substrate is provided, which is a three-dimensional porous structure formed by interwoven carbon fibers. The substrate has a thickness of 7 μm, a carbon fiber diameter of 5 μm, and a substrate density of 1.8 g / cm³. 3 The porosity of the substrate is 60%.
[0085] (2) A barrier layer was deposited on both sides of the substrate using a first magnetron sputtering process to form a nickel-chromium alloy barrier layer covering the carbon fiber surface. The average grain size of the nickel-chromium alloy was 15 nm; the mass ratio of nickel to chromium in the nickel-chromium alloy was 75:25; the first magnetron sputtering process used two nickel-chromium alloy targets, the sputtering speed was 10 m / min, and the sputtering power was 18 kW; the thickness of the final barrier layer was 12 nm.
[0086] (3) A copper seed layer is deposited on the surface of the barrier layer using a second magnetron sputtering process. The second magnetron sputtering process uses 7 copper targets, a sputtering speed of 10 m / min, a sputtering power of 18 kW, and a copper seed layer thickness of 70 nm.
[0087] (4) A copper conductive host layer was deposited on the copper seed layer using a pulse electroplating process to form a metal layer and prepare a composite current collector. The peak current density of the pulse electroplating process was 2 ASD, the average current density was 0.5 ASD, the on-time was 5 ms, the off-time was 25 ms, the duty cycle was 15%, and the electroplating time was 9 min; the final thickness of the metal layer was 1 μm.
[0088] Example 2
[0089] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0090] In step (2), the first magnetron sputtering process uses one nickel-chromium alloy target with a sputtering power of 15kW; the final barrier layer has a thickness of 5 nm.
[0091] Example 3
[0092] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0093] In step (2), the first magnetron sputtering process uses 3 nickel-chromium alloy targets with a sputtering power of 20kW; the final barrier layer has a thickness of 20 nm.
[0094] Example 4
[0095] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0096] In step (2), the first magnetron sputtering process uses 4 nickel-chromium alloy targets with a sputtering power of 23kW; the sputtering speed of the first magnetron sputtering process is adjusted so that the thickness of the final barrier layer is 22 nm.
[0097] Example 5
[0098] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0099] In step (2), the average grain size of the nickel-chromium alloy is 10 nm.
[0100] Example 6
[0101] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0102] In step (2), the average grain size of the nickel-chromium alloy is 20 nm.
[0103] Example 7
[0104] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0105] In step (2), the average grain size of the nickel-chromium alloy is 8 nm.
[0106] Example 8
[0107] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0108] In step (2), the average grain size of the nickel-chromium alloy is 22 nm.
[0109] Example 9
[0110] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0111] In step (2), the mass ratio of nickel to chromium in the nickel-chromium alloy is 70:30.
[0112] Example 10
[0113] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0114] In step (2), the mass ratio of nickel to chromium in the nickel-chromium alloy is 80:20.
[0115] Example 11
[0116] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0117] In step (2), the mass ratio of nickel to chromium in the nickel-chromium alloy is 65:35.
[0118] Example 12
[0119] The preparation method of the composite current collector provided in this embodiment is basically the same as that in Example 1, except that:
[0120] In step (4), a copper conductive substrate layer is deposited on the copper seed layer using a DC electroplating process to form a metal layer, thus preparing a composite current collector. The current density of the DC electroplating process is 0.5 ASD, the DC electroplating time is 9 min, and the final thickness of the metal layer is 1 μm.
[0121] Comparative Example 1
[0122] This comparative example provides a method for preparing a composite current collector.
[0123] (1) A substrate is provided, which is a three-dimensional porous structure formed by interwoven carbon fibers. The substrate has a thickness of 7 μm, a carbon fiber diameter of 5 μm, and a substrate density of 1.8 g / cm³. 3 The porosity of the substrate is 60%.
[0124] (2) Copper seed layers were deposited on both sides of the substrate using magnetron sputtering. The magnetron sputtering process used 7 copper targets, sputtering speed of 10 m / min, sputtering power of 18 kW, and the thickness of the copper seed layer was 70 nm.
[0125] (3) A copper conductive host layer was deposited on the copper seed layer using a pulse electroplating process to form a metal layer and prepare a composite current collector. The peak current density of the pulse electroplating process was 2 ASD, the average current density was 0.5 ASD, the on-time was 5 ms, the off-time was 25 ms, the duty cycle was 15%, and the electroplating time was 9 min; the final thickness of the metal layer was 1 μm.
[0126] Test case
[0127] The composite current collectors prepared in the above embodiments and comparative examples were subjected to the following tests:
[0128] (1) Peel strength test
[0129] The bonding force between the substrate and the metal layer was tested using a tensile testing machine (manufacturer: Jinan Saicheng Electronic Technology Co., Ltd.). The peeling speed was 300 mm / min, the sample width was 20 mm, the peeling force was recorded, and the peel strength (unit: KN / m) was calculated.
[0130] (2) Surface roughness Ra test of metal layer
[0131] The surface roughness of the metal layer was tested using a surface profilometer (manufacturer: Mitutoyo SJ410). Measurements were taken from multiple different areas and the average value was calculated. The obtained parameters are expressed as arithmetic mean roughness (Ra) (unit: μm).
[0132] The test results are shown in Table 1.
[0133] Table 1
[0134]
[0135] As shown in Table 1, comparing Examples 1-12 and Comparative Example 1, it can be seen that the composite current collector provided in this application effectively improves the bonding strength between the carbon fiber substrate and the metal layer, reduces the surface roughness of the metal layer, and thus facilitates the coating of a uniform active material layer on the metal layer.
[0136] Comparing Examples 1 and Examples 2-4, it can be seen that as the number of targets and sputtering power used in the first magnetron sputtering process are adjusted, the thickness of the barrier layer in Examples 2-4 gradually increases. In Example 4, the barrier layer is too thick, which hinders metal deposition, resulting in insufficient pore filling, increased surface roughness of the metal layer, and decreased interfacial bonding.
[0137] Comparing Examples 1 and Examples 5-8, it can be seen that when the average grain size of the nickel-chromium alloy is adjusted, the average grain size of the nickel-chromium alloy in Examples 5-6 is controlled within a suitable range. The nickel-chromium alloy provides sufficient specific surface area to provide adsorption and nucleation sites for metal filling, while avoiding complete filling of the substrate pores and reserving space for metal layer filling. In Example 7, the grain size of the nickel-chromium alloy is too small, so the barrier layer cannot completely cover the carbon fiber, resulting in a decrease in interfacial bonding force. In Example 8, the grain size of the nickel-chromium alloy is too large, which hinders metal deposition to the depth of the pores, resulting in an increase in the surface roughness of the metal layer.
[0138] Comparing Examples 1 and 9-11, it can be seen that when the proportion of nickel in the nickel-chromium alloy is adjusted, the proportion of nickel in the nickel-chromium alloy in Examples 9-10 is controlled within a suitable range, which is conducive to the formation of solid solution between nickel atoms and metal atoms in the metal layer, thereby improving the interfacial compatibility. At the same time, an appropriate amount of chromium can enable chromium atoms to react with carbon atoms on the carbon fiber surface to generate stable carbides, enhancing the interfacial bonding force and chemical stability between the carbon fiber and the barrier layer. However, since the nickel content in the nickel-chromium alloy in Example 11 is too low, it will weaken the formation of solid solution between the barrier layer and the metal layer, reduce the interfacial compatibility, and thus lead to a decrease in the peel strength between the carbon fiber substrate and the metal layer.
[0139] Comparing Example 1 and Example 12, it can be seen that since Example 12 uses a DC electroplating process to prepare the conductive substrate layer, compared with the pulse electroplating process in Example 1, the metal atoms are more likely to nucleate randomly rather than grow uniformly along the lowest energy position. This results in insufficient pore filling in the three-dimensional porous structure of the substrate film, reduced continuity and flatness of the metal layer, increased surface roughness, and reduced peel strength.
[0140] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0141] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A composite current collector, characterized in that, include: The substrate has a three-dimensional porous structure formed by interwoven carbon fibers; A barrier layer, covering the surface of the carbon fiber, the barrier layer comprising a nickel-chromium alloy; as well as A metal layer is disposed on the surface of the barrier layer away from the carbon fiber, and at least a portion of the metal layer fills the pores of the substrate.
2. The composite current collector according to claim 1, characterized in that, The nickel-chromium alloy satisfies at least one of the following conditions: (1) The average grain size of the nickel-chromium alloy is 10 nm to 20 nm; (2) The mass ratio of nickel to chromium in the nickel-chromium alloy is (70~80):(20~30).
3. The composite current collector according to claim 1, characterized in that, The metal layer includes: A seed layer is disposed on the surface of the barrier layer; and a conductive body layer is disposed on the surface of the seed layer.
4. The composite current collector according to claim 3, characterized in that, The thickness of the seed layer is 20 nm to 50 nm.
5. The composite current collector according to any one of claims 1 to 4, characterized in that, At least one of the following conditions must be met: (1) The thickness of the barrier layer is 5 nm to 20 nm; (2) The surface roughness Ra of the metal layer is less than 1 μm; (3) The thickness of the substrate is 4 μm to 10 μm; (4) The thickness of the metal layer is 0.5 μm to 2 μm; (5) The diameter of the carbon fiber is 3 μm to 7 μm; (6) The density of the substrate is 1 g / cm³. 3 ~2 g / cm 3 ; (7) The porosity of the substrate is 20%~70%.
6. A method for preparing a composite current collector, characterized in that, Includes the following steps: A substrate is provided having a three-dimensional porous structure formed by interwoven carbon fibers; A first magnetron sputtering process is used to deposit on both sides of the substrate to form a barrier layer on the surface of the carbon fiber, the barrier layer comprising a nickel-chromium alloy. A metal layer is deposited on the surface of the barrier layer away from the carbon fiber, such that the metal layer at least partially fills the pores of the three-dimensional porous structure.
7. The method for preparing the composite current collector according to claim 6, characterized in that, The first magnetron sputtering process satisfies at least one of the following conditions: (1) The number of targets in the first magnetron sputtering process is 1 to 3; (2) The sputtering power of the first magnetron sputtering process is 15 kW to 20 kW.
8. The method for preparing the composite current collector according to claim 6, characterized in that, Depositing a metal layer on the barrier layer specifically includes the following steps: A seed layer is deposited on the barrier layer using a second magnetron sputtering process; A conductive host layer is deposited on the seed layer using a pulse electroplating process.
9. The method for preparing the composite current collector according to claim 8, characterized in that, At least one of the following conditions must be met: (1) The number of targets in the second magnetron sputtering process is 4 to 10; (2) The sputtering power of the second magnetron sputtering process is 5 kW to 10 kW; (3) The peak current density of the pulse electroplating process is 1 ASD~3 ASD; (4) The average current density of the pulse electroplating process is 0.2 ASD~0.8 ASD; (5) The conduction time of the pulse electroplating process is 1 ms to 10 ms; (6) The turn-off time of the pulse electroplating process is 5 ms to 50 ms; (7) The duty cycle of the pulse electroplating process is 10%~20%.
10. A secondary battery, characterized in that, The composite current collector includes the composite current collector as described in any one of claims 1 to 5, or the composite current collector prepared by the method described in any one of claims 6 to 9.
